1980
DOI: 10.1111/j.1471-4159.1980.tb11266.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by Gangliosides of the Binding of Serotonin to Serotonin Binding Protein

Abstract: Several gangliosides, especially GD, (disialosyllactosyl ceramide) in the presence of another lipid (lecithin) were found to enhance the binding of serotonin to serotonin binding protein (SBP) severalfold. In our conditions, this enhancement was linear to a concentration of 2.7 x 1 0 -6~ GD3, and a three-to fivefold increase in binding capacity of SBP was obtained with 8.8 x M .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Similar requirements with regard to temperature, ATP, Mg2+, and sensitivity to added reserpine were observed for 5-HT uptake by rat brain synaptic vesicles (Kaladhar, 1977;Halaris and Demet, 1978). Tamir et al (1980) successfully demonstrated the presence of SBP in synaptic vesicles. In an earlier study (Tamir et al, 1976) they were able to demonstrate a specific role for Fe2+ in enhancing 5-HT binding to SBP by several-fold.…”
Section: Maintenance Of High Monoamine Concentrationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar requirements with regard to temperature, ATP, Mg2+, and sensitivity to added reserpine were observed for 5-HT uptake by rat brain synaptic vesicles (Kaladhar, 1977;Halaris and Demet, 1978). Tamir et al (1980) successfully demonstrated the presence of SBP in synaptic vesicles. In an earlier study (Tamir et al, 1976) they were able to demonstrate a specific role for Fe2+ in enhancing 5-HT binding to SBP by several-fold.…”
Section: Maintenance Of High Monoamine Concentrationsmentioning
confidence: 96%
“…Although nonhaem iron in the brain is shown to be associated with certain enzymes and compounds purified serotonin binding protein (SBP) (Tamir et al, 1976). They have demonstrated subsequently the presence of SBP in synaptic vesicles, thus suggesting a role for iron in 5-HT storage in the brain (Tamir and Gershen, 1979;Tamir et al, 1980). We have therefore undertaken studies to investigate the effects of moderate to severe iron deficiency on 5-HT uptake into rat brain synaptic vesicles in vifro, the results of which are reported in the present communication.…”
mentioning
confidence: 99%
“…Gangliosides seem to have an important role in the functioning of the 5-HT system (Tamir et al, 1980;Agnati et al, 1983;Adlersberg et al, 1987).…”
Section: Neurotrophic Factors Andmentioning
confidence: 97%
“…Gangliosides are sialic-acid-containing glycolipids present in cell membranes, where they have been implicated as receptors for cholera toxin [10], interferon [3], hormones [27,48], viruses [2,32] and growth factors [4,5]. Addition of gangliosides to cultures of human lymphocytes was shown to inhibit their responses to lectin and antigens [13,31,54] Offprint requests to: P. Hersey, Room 443, Immunology and Oncology Unit, David Maddison Clinical Sciences Building, Royal Newcastle Hospital, Newcastle, N.S.W.…”
Section: Introductionmentioning
confidence: 99%